DESIGN AND DEVELOPMENT OF A STEM-BASED AUGMENTED REALITY MODULE FOR TEACHING GLOBAL WARMING IN HIGH SCHOOLS - Nor, M.; Nasir, M. Khalid M.; Arsad, Nurazidawati M. (Veredas do Direito, 2026)
Global warming is a critical global issue that requires effective science education strategies to enhance students’ conceptual understanding and environmental awareness. One of the challenges in teaching global warming at the high school level is the abstract nature of the concepts, which often limits students’ comprehension when delivered through conventional learning media. To address this issue, this study aims to design and develop a mobile-based STEM-integrated Augmented Reality (AR) learning module on the topic of global warming and to examine its effectiveness in improving students’ learning outcomes. This study employed a research and development (R&D) design, in which the instructional product was developed using the ADDIE instructional design model, consisting of analysis, design, development, implementation, and evaluation stages. The AR module was developed as a mobile application that integrates STEM principles through interactive 3D visualizations, animations, and contextual problem-solving activities related to global warming phenomena. Content and media validation were conducted by subject-matter experts and instructional media experts using a validation instrument with a four-point Likert scale. The validation results indicated that the developed AR learning module achieved very high validity, with an average score of 3.50 for content validity and 3.65 for media validity. The effectiveness of the module was tested through a quasi-experimental design involving 68 eleventh-grade science students (Class XI MIPA) from a State Senior High School (SMAN), divided into experimental and control groups. Data were analyzed using inferential statistical tests to examine differences in learning outcomes before and after implementation. The results showed a statistically significant improvement in students’ understanding of global warming in the experimental group compared to the control group (p < 0.05), indicating that the STEM-based AR learning module positively influenced students’ learning outcomes. Based on these findings, the STEM-integrated AR mobile learning module on global warming is considered valid and pedagogically effective, and it has strong potential to be implemented as an innovative learning medium to support science education at the senior high school level.